LACE AND KNITTING IN LEMKO`S CLOTHING DECOR: ETHNIC LOCAL AND ART FEATURES - Козакевич, О. Р. (Art and Design, 2020)
Local and art features of Lemko`s region traditional clothing décor are studied. The attention is given to lace and knit décor, which gave the clothing components a unique and often was the artistic accent in Lemko clothing complexes. Methodology. The methodological basis of the study is the principle of systematic approach and comprehensive research. The comparative-historical and typological methods was used for study the research subject. The analysis of lace and knit décor was done using the art study method. Results. The main typological groups and items` types formed under the influence of ethno-cultural and historical factors were determined based on artifacts from museum collections, field studios and scientific sources. The décor made textile techniques and technological methods are outlined, with pointed of common and distinctive features in comparison with folk clothing of the Carpathian region`s other ethnographic groups. Artistic and stylistic characteristics of knitting and lace are analyzed, taking into account the interplay of neighbouring ethnicities cultures and border features. It is studied out that the lace was common in female clothing in the production of the headwear, the waist wear and shirts. Knitting items in male clothing mainly in the south- western Lemko`s territories were used. There were naracvytsias, mittens, socks, locally were used knitting hats “megerka” and scarves. In the creation of lace and knit items they used common techniques and technical methods peculiar to Hutsul`s and Boiko`s regions: knitting, crocheting gloves “on the laba”, “on the board”. Instead, the embroidery methods called “English hapt” with “cut out’ was typical only for the Lemko`s, mainly central-western, territories. Scientific novelty consists in the introduction into the scientific circulation of materials about Lemko folk clothing. The focus is on the lace and knit décor that reveals the artistic diversity of Lemko`s region clothing art. Practical significance. The study allows expanding the knowledge of Lemko traditional clothing and textile production, in particular, about the centers of made some types of clothing with openwork and knitting. This contributes to use the receives information in the further study of Lemko`s region traditional clothing.